Some similarity measures of rough interval Pythagorean fuzzy sets - V. S. Subha (Ayandegan Institute of Higher Education, 2020)
In this paper, we expose cosine, jaccard and dice similarity measures and rough interval Pythagorean mean operator. Some of the important properties of the defined similarity measures have been established. Then the proposed methods are applied for solving multi attribute decision making problems. Finally, a numerical example is solved to show the feasibility, applicability and effectiveness of the proposed strategies.